LEADERSHIP AND NATIONAL DEVELOPMENT: ESTABLISHING THE THEORETICAL NEXUS - Achor, Joy Achile (International Studies Journal)
This paper interrogated the nexus between leadership and national development mainly on a theoretical perspective. Hence leadership in a context of nation[1]building is an independent variable; it could be a determinant to national development. This paper principally used qualitative technique to interrogate the theoretical nexus of leadership as an independent variable and national development as a dependent variable. Scholars have used their different orientation to theorize the purpose of leadership in different societies. In whatever context, the qualities of a good leader are universal. In spite of the divergence perspective of scholars in theorizing leadership, the emphasis is the virtues being it moral, religious, political, economic, cultural, or otherwise; the essence is to arrive at good leadership. Thus, this paper sees leadership as an end itself but not a means to an end.